2010
DOI: 10.1007/s11120-010-9596-y
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the putative Ca2+-binding site in the light-harvesting complex 1 of thermophilic purple sulfur bacterium Thermochromatium tepidum

Abstract: The core light-harvesting complex (LH1) of purple sulfur photosynthetic bacterium Thermochromatium tepidum exhibits an unusual absorption maximum at 915 nm for the Q (y) transition, and is highly stable when copurified with reaction center (RC) in a LH1-RC complex form. In previous studies, we demonstrated that the calcium ions are involved in both the large red shift and the enhanced thermal stability, and possible Ca(2+)-binding sites were proposed. In this study, we further examine the putative binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…acidophila as template (McDermott et al 1995), the specific coordination of Ca 2? at the C-terminus of the a-subunit of LH1 has been proposed (Yu et al 2010). Amongst the amino acid atoms to bind the Ca 2?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…acidophila as template (McDermott et al 1995), the specific coordination of Ca 2? at the C-terminus of the a-subunit of LH1 has been proposed (Yu et al 2010). Amongst the amino acid atoms to bind the Ca 2?…”
Section: Resultsmentioning
confidence: 99%
“…Chromatophores were prepared as described previously (Yu et al 2010). In essence, the harvested cells were suspended in Tris-HCl (20 mM, pH 8.5) buffer and exposed to sonic oscillation.…”
Section: Purification Of Isolated Rh-lh1mentioning
confidence: 99%
“…tepidum cells were cultured for seven days. Chromatophores were prepared as previously reported [24]. The chromatophores were suspended in 0.5 mL of 20 mM Tris–HCl (pH 7.5) at concentration of A 850 = 120, and were then lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…35 Recently, it was revealed that the former is likely, based on a topological study using tepidum chromatophores and metal chelators. 54 The blue shift of the Q y bands due to Ca 2þ depletion by chelators was not induced when the native membranes were completely retained, indicating that the outside of the chromatophore does not include the metal binding site. However, once the membranes were destroyed by detergent treatments, the chelators invaded the inside of the chromatophore where the C-terminus of the LH1 R-polypeptide exists, resulting in a blue shift of the Q y bands and deterioration of the thermal stability.…”
mentioning
confidence: 97%